Effect of Vermiform Appendix Anatomical Variations on Laparoscopic Surgical Outcomes in Appendicitis: Systematic Review - Bagus Putra Sundia Denta (International Journal Labs, 2026)
The most common surgical cause of abdominal pain is appendicitis, and its diagnosis is affected by anatomical variations of the vermiform appendix. The appendix may be in different positions, but the base of the appendix is attached to the cecum. Based on positional variations, the appendix is classified as retrocecal, pelvic, anterior, or subhepatic. This study aims to evaluate the effect of anatomical variations in appendix position on laparoscopic surgical outcomes. This study uses a systematic review method following the PRISMA 2020 guidelines. Literature searches were conducted through the Scopus and Google Scholar databases for the 2016–2026 period using the PICOS framework. The selection process identified two articles that met the inclusion criteria. Both articles reported similar findings regarding anatomical variations of the appendix and surgical outcomes. The most common finding associated with each anatomical variation of the appendix during surgery was appendiceal rupture, with a higher risk observed in the subhepatic appendix position. In addition, the subhepatic appendix position requires a longer operative time compared to other appendix positions. Meanwhile, the pelvic appendix position has a higher rate of postoperative intestinal obstruction compared to other appendix positions. In conclusion, variations in the anatomical position of the appendix have differing levels of impact on surgical and postoperative outcomes, particularly in the subhepatic and pelvic positions. This is reflected in the most common complications, such as appendiceal rupture, prolonged operative time, and an increased risk of postoperative intestinal obstruction.